Traditional medicinal knowledge: answer to the post-partum healthcare needs of the tribes of chhattisgarh - NITYA SHARMA,; DR. SMITA SAHU, (International Journal of Pharma and Bio Sciences, 2016)
Traditional medicinal practices based on the use of plants account for about 85% of the primary healthcare derived globally. The gradual disappearance of the traditional practices has raised concerns, especially in the remote parts of the world, in the current scenario where the ecosystem and culture are under constant threat due to the development. The objective of this paper is revitalization of the traditional medicinal knowledge in context of the post-partum healthcare needs of the women in the Chhattisgarh state of India. The health indicators discussed show a dismal picture with the maternal mortality ratio and infant mortality ratio being alarmingly high at 275 and 52, respectively, much below the national average and unsatisfactory. This review aims to provide an overview of how medicinal plants in this area are utilized, creating the much needed critical awareness on the available traditional medicinal knowledge, folk medicines and practices that are used or can be used for the post-partum care and asserting the importance of the knowledge being passed on from one generation to the other, while providing a solution to address the post-natal health concerns by proposing suggestions for further research.